TASK-BASED LANGUAGE TEACHING IN VIETNAM: MISUNDERSTANDINGS AND SUGGESTIONS - Chi Đô Na (Tạp chí Khoa học Đại học Đà Lạt)
Task-based language teaching (TBLT) has been extensively researched and applied in many education settings due to the belief in its effectiveness in maximizing learners’ language competency. Although this issue is not a new concept in language education, misunderstandings of TBLT do exist, which leads to further misapplications of the pedagogy. Besides, the reality of teaching and learning may not make TBLT a preferred method. This paper, therefore, takes as its aims the common misunderstandings when applying TBLT in Vietnamese education settings. The author investigates how TBLT is frequently mistakenly perceived by language educators and provides suggestions on how to design language tasks with specific implications of TBLT in an EFL classroom.